2017
DOI: 10.1007/s10792-017-0522-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal aflibercept (Eylea®) on retrobulbar hemodynamics in patients with neovascular age-related macular degeneration

Abstract: Single intravitreal administration of aflibercept alters retrobulbar blood flow velocities (BFVs) in both injected and uninjected fellow eyes in the short-term period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…). More recently, this was also shown for intravitreal aflibercept (Gok & Kapti ). Lately, another paper reported significant vasoconstriction of the retinal arterioles after three monthly injections of aflibercept using a computer‐based approach (Tetikoğlu et al.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…). More recently, this was also shown for intravitreal aflibercept (Gok & Kapti ). Lately, another paper reported significant vasoconstriction of the retinal arterioles after three monthly injections of aflibercept using a computer‐based approach (Tetikoğlu et al.…”
Section: Discussionsupporting
confidence: 54%
“…Hence, enhanced and sustained effects on ocular perfusion might be anticipated. Lately, reduced retrobulbar blood flow in the ophthalmic artery, central retinal artery and posterior ciliary artery was described 1 week after Intravitreal injection of aflibercept (IVA) (Gok & Kapti ). Significant vasoconstriction of the retinal arterioles was observed by another group following three monthly injections of aflibercept (Tetikoğlu et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that anti-VEGF drugs affect the ocular circulation. It has been reported that the ocular perfusion [31][32][33] and the choroidal thickness decreased after IVA or IVBr injections [34,35]. A laser blood flowmeter was used to show that ranibizumab decreased the retinal arterial vessel diameter, velocity, and blood flow in patients with nAMD who had received fewer ranibizumab treatments [36].…”
Section: Discussionmentioning
confidence: 99%
“…CDI was also used to analyze the effects of panretinal photocoagulation on retrobulbar hemodynamics in diabetic patients, and higher blood flow velocities after treatment were detected [181]. Moreover, in neovascular age-related macular degeneration intravitreal injections of ranibizumab or aflibercept lead to reduced blood flow velocities in retrobulbar vessels [182,183].…”
Section: Clinical and Scientific Relevance Of Measuring Retrobulbar B...mentioning
confidence: 99%